2016
DOI: 10.1038/ncomms11939
|View full text |Cite
|
Sign up to set email alerts
|

A key genetic factor for fucosyllactose utilization affects infant gut microbiota development

Abstract: Recent studies have demonstrated that gut microbiota development influences infants' health and subsequent host physiology. However, the factors shaping the development of the microbiota remain poorly understood, and the mechanisms through which these factors affect gut metabolite profiles have not been extensively investigated. Here we analyse gut microbiota development of 27 infants during the first month of life. We find three distinct clusters that transition towards Bifidobacteriaceae-dominant microbiota.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
304
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 298 publications
(361 citation statements)
references
References 61 publications
22
304
2
Order By: Relevance
“…Importantly, the effects of any intervention will be affected by a variety of host and environmental factors 121 . Thus, the effects of prebiotics have the potential to vary widely on an individual basis.…”
Section: Conferring a Health Benefitmentioning
confidence: 99%
“…Importantly, the effects of any intervention will be affected by a variety of host and environmental factors 121 . Thus, the effects of prebiotics have the potential to vary widely on an individual basis.…”
Section: Conferring a Health Benefitmentioning
confidence: 99%
“…Growth on 2′-FL is strain dependent in B. breve (Ruiz-Moyano et al 2013). Matsuki et al (2016) examined bifidobacterial genomes and identified a putative fucosyllactose utilization pathway, which was associated with elevated acetate in the gut and altered microbiota composition. This work identified an ABC transporter as a component for fucosyllactose consumption in bifidobacteria (Matsuki et al 2016).…”
Section: Molecular Mechanisms Of Utilization Of Human Milk Oligosacchmentioning
confidence: 99%
“…Matsuki et al (2016) examined bifidobacterial genomes and identified a putative fucosyllactose utilization pathway, which was associated with elevated acetate in the gut and altered microbiota composition. This work identified an ABC transporter as a component for fucosyllactose consumption in bifidobacteria (Matsuki et al 2016). The fucosyllactose solute-binding protein gene associated with this ABC transporter was knocked out in a B. breve strain, and the knockout strain showed limited growth on HMO (Matsuki et al 2016).…”
Section: Molecular Mechanisms Of Utilization Of Human Milk Oligosacchmentioning
confidence: 99%
“…Bifidobacterium and Bacteroides species could metabolize HMO, but not enteric Streptococcus , Veillonella , Eubacterium , Clostridium and E. coli assuring a selectivity of HMO as growth promoter for specific bacteria (Marcobal et al ., 2010). Considerable differences in HMO utilization exist among infant bifidobacteria opening opportunities for fine tuning with HMO (Matsuki et al ., 2016). Different Bifidobacterium or Bacteroides isolates followed different enzymatic strategies of either intracellular or extracellular HMO digestion.…”
Section: Biome Engineering: Modifying the Nutrient Inputmentioning
confidence: 99%